First Experience with the LVAD CorHeart 6 System in Ukraine: A Bridge to Heart Transplantation (BTT), Preliminary 4-Month Results - Volodymyr G. Tanskyi (Transplantation and artificial organs, 2025)
Aim. The range of mechanical circulatory support (MCS) devices used for two-stage heart transplantation (HT) is quite wide – starting from the implantation of an artificial heart (TAH), biventricular bypass (BiVAD), left ventricular bypass (LVAD) and ending with the connection of an extracorporeal membrane oxygenation (ECMO) system. The duration of use of these technologies depends on the chosen MCS method. In particular, LVAD using implanted pumps involves long-term connection of the systems (from a month to several years). The advantage of such systems is the ability for the patient to leave the clinic and maintain an active lifestyle.Objective. We present the first experience of implantation of the CorHeart 6 LVAD system in Ukraine. We retrospectively collected preoperative information, treatment course, and clinical outcomes.Conclusions. LVAD systems are the most effective "bridge" to transplantation, because:- unload damaged ventricles of the heart: reduce the size, volume and mass of the ventricles;- provide effective circulatory support;- preserve and improve the functioning of organs and systems,- prevent the development of complications of CHF;- increase survival, significantly improve the quality of life and functional status of patients compared to drug therapy.